Analisis Motivasi Kerja Dalam Upaya Meningkatkan Disiplin Kerja Karyawan - Rosti Setiawati; Indah Bernita (LPPM Universitas Koperasi Indonesia, 2026)
Analysis of Work Motivation in an Effort to Improve Employee Work Discipline: A Case Study of Employees at the Primkoppol Satbrimob Polda Jabar, Sumedang Regency Research. This study aims to determine the work motivation and work discipline of employees at the Primkoppol Satbrimob Polda Jabar and the efforts cooperatives should take to provide work motivation to improve employee discipline. The research method used a case study, describing each indicator of employee work motivation and discipline. Data collection included observation, interviews, and questionnaires on employee work motivation and discipline, as well as literature review. The results of the study indicate that work motivation plays a crucial role in improving employee work discipline, and that employee work discipline at the Primkoppol Satbrimob Polda Jabar is quite good.